Donor NK cell licensing in control of malignancy in hematopoietic stem cell transplant recipients. Issue 10 (27th August 2014) - Nowak, Jacek; Kościńska, Katarzyna; Mika‐Witkowska, Renata; Rogatko‐Koroś, Marta; Mizia, Sylwia; Jaskuła, Emilia; Polak, Małgorzata; Mordak‐Domagała, Monika; Lange, Janusz; Gronkowska, Anna; Jędrzejczak, Wiesław Wiktor; Kyrcz‐Krzemień, Sławomira; et al.
<x xml:space="preserve">Abstract</x> Among cancers treated with allogeneic hematopoietic stem‐cell transplantation (HSCT), some are sensitive to natural killer (NK) cell reactivity, described as the "missing self" recognition effect. However, this model disregarded the NK cell licensing effect, which highly increases the NK cell reactivity against tumor and is dependent on the coexpression of inhibitory killer cell immunoglobulin‐like receptor (iKIR) and its corresponding HLA Class I ligand. We assessed clinical data, HLA and donor iKIR genotyping in 283 patients with myelo‐ and lymphoproliferative malignancies who underwent HSCT from unrelated donors. We found dramatically reduced overall survival (OS), progression free survival (PFS), and time to progression (TTP) among patients with malignant diseases with the lack of HLA ligand cognate with this iKIR involved in NK cell licensing in corresponding donor (events 83.3% vs. 39.8%, P = 0.0010; 91.6% vs. 47.7%, P = 0.00010; and 30.0% vs. 17.3%, P = 0.013, for OS, PFS, and TTP, respectively). The extremely adverse PFS have withstand the correction when patient group was restricted to HLA mismatched donor‐recipient pairs. The incidence of aGvHD was comparable in two groups of patients. In malignant patients after HSCT the missing HLA ligand for iKIR involved in NK cell licensing in corresponding donor ("missing licensing proof") induced extremely adverse survival of the patients due to the progression of malignancy and not to the aGvHD. Avoiding the selection of HSCT donors with the "missing licensing proof" in the malignant patient is strongly advisable.Am. J. Hematol. 89:E176–E183, 2014. © 2014 Wiley Periodicals, Inc.